COMUNIDADES TRADICIONAIS DE FAXINAIS E GESTÃO DE POLÍTICAS PÚBLICAS EDUCACIONAIS NO ESTADO DO PARANÁ: COMPREENDENDO TERRITÓRIOS E TERRITORIALIDADES - Simões, Willian (2009)
This work proposes to understand the impacts of Educational Public Policy territorialization in Faxinais Traditional Communities of Paraná State. To perform this, it became necessary the experience of living in a faxinalense community: the Community Taquari dos Ribeiros. Living in this community, located in Rio Azul city in Paraná State, it was verified the existence of a Municipal School in the community, allowing students to conclude the initial years (1st to 4th series) and the students displacement through the school transportation to conclude the final years of Elementary School (5th to 8th series) as well as High School in downtown. From this fact, some important questionings began to guide the development of this research. Therefore, this dissertation is organized in four chapters. In Chapter I, sought to assemble a theoretical and conceptual, like the concepts of territory, (multi) territoriality, de (re) territorialization. Soon after, get the context in which Faxinais Traditional Communities of Paraná State get visibility in the state and in different civil society organizations, followed by a discussion about territory specificity and (multi) territoriality (ies) of faxinalenses. In Chapter II, there is an approach with the Management of Educational Public Policy, especially, policies aiming field communities, understanding that there are two opposite conceptions of Education: Rural Education and the Education Field. This is a discussion between the legal bases (laws and constitutions) and different historical and territorial contexts of the rural Brazil. Then, in Chapter III, the emphasis is given on the Management of Educational Public Policy carried out in the Paraná State and its impacts in rural territories in particular and, more generally, in the Faxinais Traditional Communities. Finally, in Chapter IV, a resumption of reality apprehended and questioned in Taquari dos Ribeiros, with a greater rapprochement with different community members, especially a specific audience: the young faxinalenses. They, on the territory in which they live, indicated their wishes in the present and perspectives for the future.